2006
DOI: 10.2337/dc06-0665
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight Loss and Nutritional Intervention on Arterial Stiffness in Type 2 Diabetes

Abstract: OBJECTIVE -There is increased stiffness of the large central arteries in type 2 diabetic patients, and obesity is a risk factor. However, the effect of intentional weight loss on arterial stiffness is uncertain, and the purpose of the current study was to assess this effect.RESEARCH DESIGN AND METHODS -Arterial stiffness was assessed by measuring aortic pulse wave velocity (aPWV) at baseline and at completion of a 1-year weight loss intervention. Metabolic control of type 2 diabetes was also appraised.RESULTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 33 publications
6
43
3
Order By: Relevance
“…From prior studies, it appears that weight loss of >7% may improve arterial stiffness and BP. This amount of weight loss was also associated with improvement in lipid profile, inflammatory markers, and insulin sensitivity [7,22,37] achieved by a regimented nutritional and exercise intervention program [6]. Despite the improvement in hsCRP and insulin parameters, it is possible that the small weight loss achieved in this study and lack of improvement in lipid profile were not sufficient to improve arterial stiffness in our study.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…From prior studies, it appears that weight loss of >7% may improve arterial stiffness and BP. This amount of weight loss was also associated with improvement in lipid profile, inflammatory markers, and insulin sensitivity [7,22,37] achieved by a regimented nutritional and exercise intervention program [6]. Despite the improvement in hsCRP and insulin parameters, it is possible that the small weight loss achieved in this study and lack of improvement in lipid profile were not sufficient to improve arterial stiffness in our study.…”
Section: Discussioncontrasting
confidence: 45%
“…Metabolic risk parameters, which were insulin sensitivity and resistance measured in this study both significantly improved during the 9 months intervention. Several studies reported weight loss ranging from 7% to 10% were able to improve insulin sensitivity and resistance [7,[22][23][24]. In the current study, fasting insulin level, insulin sensitivity and resistance were improved after 9 months intervention despite a small weight loss of 2.9% with no significant changes seen in FPG and lipid profile.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…One of the manifestations of subclinical vascular disease is arterial stiffness, which represents a loss of compliance and elasticity within large arteries. 5) In diabetes, recent evidence indicates that increased arterial stiffness, involving accelerated vascular aging of the aorta, is a powerful risk factor for early mortality. Arterial wall stiffening is exacerbated in common carotid and femoral arteries by diabetes.…”
Section: Effects Of Grape Seed Proanthocyanidin Extracts On Aortic Pumentioning
confidence: 99%
“…The present study adds to a number of investigations, which have consistently shown a reduction in cfPWV over the short term, following different lifestyle interventions, including not only physical exercise [11][12][13][14][15][16] but also weight loss, smoking cessation and salt intake restriction [17][18][19][20][21][22][23][24][25] (Table 1).…”
mentioning
confidence: 92%